2020
DOI: 10.1039/d0sm00080a
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering friction dynamics using hydrogel particles as soft ball bearings

Abstract: Hydrogel microparticles transition through four rate-dependent regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…The samples in the current study, pureed carrot matrices, are inhomogeneous suspensions with particles of carrot as well as starch granules (in the starch‐based samples). A bell‐shaped friction profile, indicative of particle entrainment, similar to this result has been observed earlier in various studies such as starch pastes (Zinoviadou, Janssen, & de Jongh, 2008), soft gels (Gabriele, Spyropoulos, & Norton, 2010), maize starch granules (Zhang et al, 2017), yogurt (Nguyen et al, 2017), and gelatin microparticle suspensions (Rudge, van de Sande, Dijksman, & Scholten, 2020).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The samples in the current study, pureed carrot matrices, are inhomogeneous suspensions with particles of carrot as well as starch granules (in the starch‐based samples). A bell‐shaped friction profile, indicative of particle entrainment, similar to this result has been observed earlier in various studies such as starch pastes (Zinoviadou, Janssen, & de Jongh, 2008), soft gels (Gabriele, Spyropoulos, & Norton, 2010), maize starch granules (Zhang et al, 2017), yogurt (Nguyen et al, 2017), and gelatin microparticle suspensions (Rudge, van de Sande, Dijksman, & Scholten, 2020).…”
Section: Resultssupporting
confidence: 85%
“…Suebsaen, Suksatit, Kanha, and Laokuldilok (2019) found that elderly with dysphagia preferred gel foods with high tan δ for ease of swallowing. studies such as starch pastes (Zinoviadou, Janssen, & de Jongh, 2008), soft gels (Gabriele, Spyropoulos, & Norton, 2010), maize starch granules (Zhang et al, 2017), yogurt (Nguyen et al, 2017), and gelatin microparticle suspensions (Rudge, van de Sande, Dijksman, & Scholten, 2020).…”
Section: Viscoelastic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tribological experiment was conducted under reciprocating friction modes to investigate the lubrication property of MGSs and MGS@DMA‐SBMA ( Figure g). As shown in Figure 2a–d, compared to phosphate buffered saline (PBS) with a friction coefficient (COF) value of 0.032, the COF values of MGSs significantly decreased (≈25% reduction) under 5, 8, and 10 N, indicating certain lubricating performance of the viscoelastic MGSs themselves due to the ball‐bearing effect, [ 35 ] which was consistent with the results in the previous study that microgels served as viscosity modifiers for enhancing lubrication performance of buffer solution or low viscosity medium. [ 18 ] In addition, with surface grafting of DMA‐SBMA copolymer, the COF values of MGS@DMA‐SBMA further decreased by 11% compared to the COF values of MGSs under 5 and 10 N. Typically, the SMBA brush in the DMA‐SBMA copolymer stretched well under low load in aqueous solution, while being damaged under a relatively higher load, and resulting in the increased COF value.…”
Section: Resultsmentioning
confidence: 99%
“…This should be ascribed to the fact that the particle size of the microgels shrank at higher temperature due to the hydrophobic interaction of the molecular chain, which makes the microgels could easier to enter into the narrow sliding interfaces. Then, the microgel nanoparticles paly soft micro ball-bearing roles between the rubbing pairs (Xu et al, 2019a(Xu et al, , 2019bRudge et al, 2020;Xu et al, 2022). When the temperature exceeded the LCST of the microgels, the nanoparticle size decreased significantly, which helps more microgel additives play the lubrication role, thus the friction coefficient decreased dramatically.…”
Section: Temperature-sensitive Lubrication Behaviormentioning
confidence: 99%